Credit usage among the un(der) banked: consumer socio-economic characteristics and influence of financial technology. (28th July 2020) - Ntwiga, Davis Bundi
We use the 2016 FinAccess Household survey data of 2015 from 8665 households to analyse how the socio-economic characteristics and financial literacy of un(der) banked consumers can shape their dynamics towards credit usage. A qualitative analysis is presented on the influence of financial technology on consumer credit usage. The access to financial services is influenced by the socio-economic characteristics and financial literacy of the consumers. Gender, financial literacy, age, income, marital status, education level and geographical cluster are statistically significant in influencing credit usage, both current and past usage relative to never had credit. As financial technology continues to expand and offer credit, there is need to understand the user experience to match their social and economic status as a means to increase credit usage in Kenya.